Pharmacological Action of a Pregnane Glycoside, Russelioside B, in Dietary Obese Rats: Impact on Weight Gain and Energy Expenditure - Abdel-Sattar, Essam; Mehanna, Eman T.; El-Ghaiesh, Sabah H.; Mohammad, Hala M. F.; Elgendy, Hanan A.; Zaitone, Sawsan A. (Frontiers in Pharmacology, 2018)
Abstract Background and purpose: Russelioside B (RB) is a pregnane glycoside obtained from Caralluma quadrangula; a herb with antidiabetic, anti-inflammatory and antihyperlipidemic activities. The present experiment tested the possible role of russelioside B in controlling weight gain in rats fed on high-fat (HF) diet. Methods: RB was separated from the n-butanol fraction of the crude methanolic extract by chromatographic separation on a Si gel column according to the procedures described previously. The experiment of the biological assessment of RB used thirty-two male Wistar rats (4 groups, n; 8). Group 1: rats were fed with a palatable normal diet. Group 2, 3 and 4 were fed on HF diet for sixteen weeks. Group 2 served as the HF diet control group while Group 3 & 4 received daily oral doses of RB (25 and 50 mg/kg) during the last four weeks. Animals' parameters like weight gain, fasting level of blood sugar, serum lipids and serum liver enzyme activities were measured. Liver or adipose tissue weight was divided by the rat’s body weight and multiplied by 100 to obtain the liver or adipose tissue index, respectively. Adipose tissues were processed for histopathological examination, measurement of mRNA expression of visfatin, leptin, adiponectin, uncoupling protein-1 (UCP-1) and carnitine palmitoyl transferase-1 (CPT-1). Furthermore, serum levels of insulin, interleukin-6 (IL-6), IL-1 tumor necrosis factor-α (TNF-α), leptin, resistin and adiponectin were assessed using ELISA kits. Results: Rats fed with the HF diet exhibited significant body weight gain, abnormal liver function, disturbed lipid profile, greater serum level of pro-inflammatory cytokines in addition to greater insulin resistance, adipose tissue and liver indices. Further, rats fed with the HF diet displayed upregulations in the expression of visfatin and leptin with down-regulations in the expression of adiponectin, UCP-1 and CPT-1 compared to normal rats. Interestingly, RB (25 or 50 mg/kg) favorably modulated the measured parameters. Conclusion: Data from this study documented the beneficial role of RB in diminishing weight gain, improving the inflammatory perturbations and energy expenditure in HF diet fed rats. Therefore, russelioside B might be a promising candidate for obesity.